Desain Pengembangan Kurikulum Integratif - Husniyatus Salamah Zainiyati (Nadwa: Jurnal Pendidikan Islam, 2014)
Implementation of an integrated curriculum in UIN Maliki seeks to provide basic competencies of Islamic sciences as a characteristic of UIN, as well as the foun-dation for the development of fields of study are developed on existing majors. Study program ta'lim al-afkar al-Islamiyyah and ta'lim al-Qur’an not only dis-cuss the matter as Fiqh, Sufism, Aqeedah, but the study needs to be developed by taking the material Qur'an and Hadith relating to the development of science and technology. Basic Islamic knowledge can be used for students or faculty development studies field according to the respective department. The program not only as a prerequisite studies program at UIN Islamic subjects, but can be used to support other subjects. Ma'had tradition intended to form the character of students and develop Islamic culture on campus. Abstrak Implementasi kurikulum integratif di UIN Maliki Malang berupaya memberi-kan kompetensi dasar ilmu-ilmu keislaman sebagai ciri khas UIN, sekaligus se-bagai landasan bagi pengembangan bidang-bidang studi yang dikembangkan pada jurusan yang ada. Program kajian ta’lim al-afkar al-Islamiyyah dan ta’lim al-Quran tidak hanya membahas materi seperti fiqh, tasawuf, aqidah, tetapi kajian perlu dikembangkan dengan mengambil materi Quran dan Hadis yang berhubungan dengan perkembangan sains dan teknologi. Dasar ilmu keislaman tersebut dapat digunakan mahasiswa atau dosen untuk pengembangan bidang kajian sesuai dengan jurusannya masing-masing. Program kajian tidak hanya se-bagai prasyarat memprogram mata kuliah keislaman di UIN, akan tetapi bisa digunakan sebagai penunjang mata kuliah lainnya. Tradisi ma’had ditujukan un-tuk membentuk karakter mahasiswa dan mengembangkan kultur Islami di kam-pus.